Edukasi Tentang Anemia Terhadap Peningkatan Pengetahuan Ibu Hamil Untuk Pencegahan Anemia Di Dusun 1 Desa Tanjung Anom Tahun 2022 - Patricia Olivine Aprilis Hutapea; Dwi Argita Br Tarigan; Junita Putri Malem Br Barus; Agusdin Triade M Gea; Chani Lya E Sianipar; Isabella T. Sembiring (BADAN PENERBIT STIEPARI PRESS, 2022)
Anemia in pregnant women is a problem both globally and in Indonesia. The prevalence of anemia in pregnant women worldwide is 41.8%, while the prevalence of pregnant women according to the 2018 Basic Health Research (RISKESDAS) is higher than the WHO prevalence at 48.9%. Community service activities carried out by lecturers and students from a university aim to provide education about the importance of iron consumption for pregnant women in Dusun 1, Tanjung Anom Village. Through problem identification, program planning, program implementation, and evaluation, an educational program including counseling, workshops, and distribution of informative materials is conducted. The evaluation results show a significant improvement in knowledge and practices of iron consumption among pregnant women. This activity is expected to contribute to reducing the incidence of anemia and improving the health of pregnant women in the area through collaboration between universities, healthcare professionals, and the community.